Korelasi Pendidikan Jiwa dalam Perspektif Ibnu Qayyim al-Jauziyyah dengan Kondisi Masyarakat Zaman Sekarang - Mustamik, Mustamik (TSAQOFAH, 2025)
Spiritual education (tazkiyatun nafs) is a fundamental aspect in shaping individual character and morality, particularly in addressing the social and spiritual challenges of modern society. This study aims to explore the correlation between the concept of spiritual education according to Ibn Qayyim al-Jawziyyah and the current conditions of contemporary society, which is experiencing moral degradation, identity crises, and spiritual alienation. The research employs a qualitative library-based method with a content analysis approach focusing on Ibn Qayyim’s works. The findings indicate that Ibn Qayyim’s concept of tazkiyatun nafs is grounded in the strengthening of faith, spiritual awareness, control of base desires, and habituation of righteous deeds. This concept emphasizes the importance of balancing cognitive, emotional, and spiritual aspects in forming a holistic personality. The relevance of Ibn Qayyim’s thought is evident in today’s society, which often neglects the spiritual dimension of education, leading to a sense of emptiness and life disorientation. The study concludes that Islamic spiritual education, from Ibn Qayyim’s perspective, holds great potential as a solution to the current moral and spiritual crisis. Its implication is that tazkiyatun nafs values should be systematically integrated into the education system and social life to cultivate a society that is intellectually and spiritually balanced.